PENERAPAN PENCEGAHAN HIPERTENSI BERBASIS APLIKASI DIGITAL MELALUI PEMBERDAYAAN PADA KELUARGA DAN MASYARAKAT DI DESA PASAR JATI WILAYAH KERJA PUSKESMAS ASTAMBUL: - - Parellangi; Ainun Sajidah; Hammad; Utama, Richko Dharmadi; Muhammad Rasyid; Azhima, Rizkan (UPPM Poltekkes Kemenkes Banjarmasin, 2025)
The prevalence of hypertension in Indonesia has continued to increase significantly, from 25.8% in 2013 to 34.11% in 2018. In South Kalimantan Province, hypertension is one of the leading causes of death, particularly among women, with an incidence rate reaching 55.8% in 2022. Banjar Regency ranks second highest in the province, with a prevalence rate of 90.3%, indicating the urgent need for more effective preventive interventions. Low public awareness and knowledge regarding the risks of hypertension are major contributing factors to the high morbidity rate. This community service program aimed to improve the knowledge and skills of health cadres and family members who accompany individuals with hypertension through a digital application-based educational approach. The program was conducted over four months and involved 24 respondents, consisting of health cadres and family caregivers, through a series of interventions including training, digital application implementation, as well as monitoring and evaluation. The results of the Wilcoxon Signed Ranks Test showed that the intervention did not have a statistically significant effect on the knowledge of family caregivers (p = 0.083), but it had a significant impact on improving the knowledge and skills of the health cadres (p = 0.036). These findings suggest that empowering health cadres through digital education can be an effective strategy to reduce hypertension incidence in the community. The results emphasize the importance of transforming health education into a more adaptive, interactive digital approach aligned with the technological usage trends among the productive-age population. Keyword: hypertension, health cadres, digital application, health education